Study of enhanced DCF (EDCF) in multimedia application - Ismail, Ismahani (2005)
IEEE 802.11e Medium Access Control (MAC) is an emerging supplement to the IEEE 802.11 Wireless Local Area Network (WLAN) standard to support Quality-of-Service (QOS). The 802.11e MAC is based on both centrally-controlled and contention-based channel accesses. This project is aimed towards evaluating the contention-based channel access mechanism, called Enhanced Distributed Coordination Function (EDCF), in comparison with the 802.11 legacy MAC, Distributed Coordination Function. Then, by using EDCF model, the acceptable number of streams for traffic type individually and combination of all traffics are determined based on ITU-T requirements. Three different types of traffic are considered namely, voice, video and data. The evaluation was done using ns-2 simulator (version 2.26) running on Linux Fedora Core 2. The metrics used in the evaluation are throughput (Byte), delay (sec) and packet loss (%). Depending on graphs of these three metrics, the performance of EDCF and DCF are evaluated, and also the numbers of stream that fulfil the ITU-T requirements are determined. Through this simulation study, a summary can be made of that EDCF can provide differentiated channel access for different traffic types. Simulation results show that EDCF performs better performance than legacy DCF. Depending on ITU-T requirements especially for delay and packet loss, the acceptable number of streams both for traffic type individually and combination of all traffics type can be determined under EDCF model.